TINGKAT PENGETAHUAN MASYARAKAT TENTANG PENGARUH POLUSI UDARA TERHADAP PENYAKIT ISPA DI PUSKESMAS PERAWATAN BETUNGAN KOTA BENGKULU - Astuti, Sinarti Juni (Journal of Nursing and Public Health, 2018)
The pollution problem is a problem that is dangerous to human life activity both inside and outside the room. Air pollution has negative implications for human health in general. Air pollution can trigger diseases such as respiratory tract infections which are larger, in India it is estimated about 80% of children suffered Acute Respiratory Infection ISPA due to air pollution while in Indonesia is estimated at about 89,526,421 people at risk from air pollution, thus increasing the risk of lung disease including ARI (Hidayat, 2012). The purpose of this study was to determine the Correlation between the Level of Public Knowledge about the Effects of Air Pollution on Respiratory Diseases in Betungan Bengkulu City District. This study is a descriptive quantitative research with cross sectional design. The population were all the people who have ISPA in Bentungan health center. The samples were taken by using accidental sampling. Data collection was done by using the questionnaire and univariate and bivariate analysis.The study showed that a small portion of the 23 respondents (24.5%), had less knowledge about the effects of air pollution, most of the respondents of 45 (47.9%) experienced ARI. Statistical tests P â‰¤ 0.05 0,000 revealed that there was a significant relationship between the level of public knowledge about the effects of air pollution on respiratory diseases Betungan health center in Bengkulu city. Expected to the health center can improve the socialization of the impact of air pollution on ISPA to society by doing routine counseling outreach to the community, particularly the women.